2016
DOI: 10.1111/dmcn.13291
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and discriminant validity of ataxia rating scales in early onset ataxia

Abstract: In patients with EOA, the reliability of ataxia rating scales is high. However, the discriminative validity for 'ataxia' is low. For adequate interpretation of ataxia rating scale scores, application in uniform movement disorder phenotypes is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 25 publications
1
32
0
2
Order By: Relevance
“…EOA refers to a group of rare heterogeneous disorders, mostly of recessively heritable origins, associated with the presentation of ataxic features before the age of 25 years . Individual patients with EOA may reveal heterogeneous ‘ataxic’ motor phenotypes, presenting ataxia as: (1) a solitary main symptom; (2) a main symptom in association with other comorbid movement disorder features; (3) a comorbid symptom, dominated by other prevailing movement disorder features, such as dystonia, chorea, or myoclonus; and (4) a stable and hardly discernible feature.…”
mentioning
confidence: 99%
“…EOA refers to a group of rare heterogeneous disorders, mostly of recessively heritable origins, associated with the presentation of ataxic features before the age of 25 years . Individual patients with EOA may reveal heterogeneous ‘ataxic’ motor phenotypes, presenting ataxia as: (1) a solitary main symptom; (2) a main symptom in association with other comorbid movement disorder features; (3) a comorbid symptom, dominated by other prevailing movement disorder features, such as dystonia, chorea, or myoclonus; and (4) a stable and hardly discernible feature.…”
mentioning
confidence: 99%
“…This scale comprises eight items: gait (scores: 0‐8), stance (0‐6), sitting (0‐4), speech disturbance (0‐6), finger chase (0‐4), nose‐finger test (0‐4), rapid alternating hand movements (0‐4), and heel‐shin slide (0‐4). SARA has been translated into several languages and is used to evaluate both the limbs and trunk; it is therefore considered a comprehensive scale for ataxia and is currently in wide use . However, the reliability of the SARA remains controversial.…”
Section: Behavioral Assessments Of Pmdsmentioning
confidence: 99%
“…SARA has been translated into several languages 76 and is used to evaluate both the limbs and trunk; it is therefore considered a comprehensive scale for ataxia and is currently in wide use. 77 However, the reliability of the SARA remains controversial. Some studies have confirmed the validity of this scale for Friedreich's ataxia, 78 spinocerebellar ataxia, 75 and posterior fossa tumor.…”
Section: Ataxiamentioning
confidence: 99%
“…Brandsma et al presented a cross‐sectional study that evaluated psychometric properties of ataxia rating scales (ARS) in EOA with ataxia as core feature (26 individuals) and as a comorbid manifestation (12 individuals whose core features were dystonia, chorea, spasticity, and myoclonus). Their rationale was that fluctuations in ARS scores should be better understood before going on to innovative treatments for EOA in randomized clinical trials (RCT).…”
mentioning
confidence: 99%
“…Defining which instrument best evaluates EOA is a very important question in designing multicenter databases, longitudinal studies, and RCTs aimed to assess disease‐modifying and/or symptomatic effects. It is worth remembering that Brandsma et al focused on instruments whose construct only evaluated ataxia and that responsivity to change between groups was not among their aims. ARS were not compared to scales developed for specific EOA disorders like the Ataxia‐Telangiectasia Neurological Examination Scale Toolkit and Friedreich Ataxia Rating Scale (FARS).…”
mentioning
confidence: 99%